사고와 표현 토론 수업에 대한 학습자의 인식과 문제 진단 - 황혜영(Hwang, Hye-young); 한혜령(Hahn, Hye-Ryeong) (교양교육연구, 2019)
사고와 표현은 급변하는 현대사회에서 요구되는 종합적 사고력과 문제해결능력과 의사소통능 력을 함양하도록 대학교양에 개설된 학제간 학문이다. 사고와 표현에서 자신의 생각을 효과적으 로 표현하는 방법으로 크게 글쓰기와 말하기 학습을 활용한다. 토론을 중심으로 한 말하기 사고 와 표현 수업에서 학생들이 토론을 어려워하는 경우가 많다. 그동안 토론 수업의 어려움에 대한 여러 관점의 연구들이 소개되고 있으나 학생들이 토론 수업을 구체적으로 어떻게 인식하는지에 대해 구체적인 데이터에 기반 한 계량화된 연구와 질적 연구과 보완된 체계적인 연구가 상세히 소 개되고 있지 않다. 본 연구는 사고와 표현의 토론에 대한 학생들의 인식과 학생들이 토론에 대해 어려워하는 점을 조사하여 토론수업의 문제를 진단해보는 것을 목적으로 한다. 토론식 수업에 대해 학생들이 어떻게 생각하는지를 조사하여 학생 입장의 토론 수업 문제 진 단을 하기 위해 사고와 표현 수업 수강생 141명 대상으로 대학 수업에 대한 흥미도와 교양필수 사고와 표현 과목에 대한 흥미도, 강의식 수업과 토론식 수업에 대한 흥미도와 편하게 느끼는 정 도, 모둠 학습과 개별 학습에 대한 선호도 그리고 강의식 수업이나 토론식 수업이 사고력과 표현 력 향상에 어느 정도 도움이 된다고 느끼는지에 대한 의견, 어렵더라도 생각과 표현력 향상에 도 움이 되면 배울 의사가 있는지 여부에 대해 11개 항목 객관식 질문 문항과 사고와 표현 수업에서 좋았던 점이나 만족스러웠던 점, 사고와 표현 수업에서 불만인 점이나 힘들었던 점, 토론식 수업 에서 힘든 점에 대해 그리고 사고와 표현 수업에서 다루었으면 하는 내용에 대해 자유롭게 기술 하는 4개 항목 주관식 질문 문항으로 설문을 진행하였다. 척도 형 설문 항목의 통계 결과와 항목 간의 상관관계를 조사한 결과를 보면 학생들의 대학 수 업에 대한 흥미는 대체로 높은 편이나 사고와 표현에 대한 흥미는 대학 수업에 대한 흥미보다는 낮게 나왔으며, 학생들은 토론식 수업보다 강의식 수업에 더 흥미를 느끼고 또 더 편하게 느끼는 것으로 나왔으며 모둠활동보다는 혼자서 하는 활동을 더 좋아하고 있는 것으로 나타났다. 그러 나 강의식 수업보다 토론식 수업이 사고력과 표현력을 키우는 데 더 도움이 된다고 생각하는 것으로 나타났으며 어렵더라도 사고력과 표현력 발전에 도움이 되는 내용을 배우고 싶은지에 대해 긍정적인 대답을 보여주었다. 개방형 문항에서 토론을 통한 논리적 사고 전개, 자기표현과 주장 연습, 타인 의견 경청 등을 수업의 장점으로, 주제적 측면, 토론 형식, 토론 경험 부족 및 성격적 특성으로 인한 부담감을 어려움으로 표명하였으며, 흥미와 관심이 높은 주제 선정, 토론 방식 개 선, 흥미 있는 다른 활동 등을 제안 사항으로 답하였다. 이 연구의 결과는 본 강의의 취지와 교 육 목적이 효과적으로 달성되기 위해서는 동기 부여, 다양한 교수법 개발과 적용, 유익하면서 흥 미 있는 내용의 발굴 등 다각도의 강의 개선 노력이 필요함을 시사해준다. “Thinking and Expression” is an interdisciplinary course that aims to help university students to develop comprehensive thinking ability, problem solving ability, and communication ability required in a rapidly changing modern society. The course is generally composed of two major components—speaking and writing—the first of which, speaking, is the focus the present paper. To be specific, we explore the difficulties experienced by students in debate-based speaking classes. While there has been a growing body of research on problems related to running debate classes, there has hardly been systematic research based on concrete quantitative and qualitative data on how debate classes are actually perceived by students. The purpose of this study is to examine the students’ perceptions of the “Thinking and Expression” and to explore the problems with debatecentered classes, which is the core component of the course, from a student perspective. In order to investigate how students think about the debate class, the present study conducted a questionnaire survey. A total of 141 students in the “Thinking and Expression” classes participated in the survey, and responded to eleven 4-point Likert-scale questions and four open-ended questions. The Likert-scale questions asked the students to rate their degree of interest in the “Thinking and Expression” course and their preference for and (dis)comfort with debate classes and lecture classes, their preference for group learning and individual learning, their perceived value of the “thinking and expression” course and lecture-based learning, and their willingness to learn to improve their thinking and expressive ability. The open-ended questions asked the participants to provide narrative answers about good aspects and unsatisfactory aspects of the class as well as suggestions or the course. The statistic analyses of the students’ responses to the questionniaire showed that the students’ interest in university courses in general was moderately high but that their interest in “Thinking and Expression” was lower than that in university courses in general. The students were found to feel more interested and comfortable in lecture-centered classes and individual activities than debate classes and group activities. They answered that they feel more comfortable with individual activities than with group activities. However, the students were found to perceive a debate class as more helpful than a lecture class in developing thinking and expressive ability. Importantly, they were also found to be rather willing to take courses that help them develop thinking and expressive ability even if they might pose difficulties. The qualitative analyses of the students’ narrative answers revealed negative cognitive and affective factors underlying debate classes, including the burden of being unable to answer in public speech and debate; discomfort with confronting others as well as being confronted by others; difficulties with working in groups; and dealing with unfamiliar or difficult topics. The findings suggest that it is necessary for instructors to develop various techniques to reduce negative affective and cognitive effects involved in debate classes and facilitate open and lively debate, in order to fully achieve the purpose of the course. KCI Citation Count: 3